Does the Clarity of Inflation Reports Affect Volatility in Financial Markets? - Bulir, Ales (IMF Working Papers; Working Paper ;, 2014)
We study whether clarity of central bank inflation reports affects return volatility in financial markets. We measure clarity of reports by the Czech National Bank, the European Central Bank, the Bank of England, and Sveriges Riksbank using the Flesch-Kincaid grade level, a standard readability measure. We find some evidence, mainly for the euro area, of a negative relationship between clarity and market volatility prior to and during the early stage of the global financial crisis. As the crisis unfolded, there is no longer robust evidence of a negative connection. We conclude that reducing noise using clear reports is possible but not without challenges, especially in times of crisis.